Development and evaluation of field methods for ammonia in air. - Rudling, J.; Hallberg, B. O.; Hultengren, May; Hultman, A. (Scandinavian Journal of Work, Environment & Health, 1984)
Three methods for measuring ammonia in air have been evaluated. Filters impregnated with 10% (volume/volume) phosphoric acid in methanol were used for two methods. Sampling was done either with a filter cassette connected to a pump or with the filters placed in a passive monitor (Gasbadge). The filters were leached with distilled water after the sampling and analyzed with ion chromatography or colorimetry (Nessler). The third method tested was a colorimetric air-monitoring badge system (ProTek). The tests showed that the accuracy of the filter methods is good and that the results are not affected by humidity. If ion chromatography is used for the analysis, amines do not interfere. The Gasbadge monitors increased their uptake when the air velocity over the sampler was raised from 0.2 to 1.0 m/s. The accuracy of the ProTek method was poor, the method was biased, and blank samples showed high values. In field tests carried out in a foundry and at a fertilizer plant, the agreement between the filter methods was good, whereas the results of the ProTek method deviated drastically from those of the other methods.